Analisis Profesionalisme Guru SMA Negeri 3 Maluku Tengah - Beatrix Tomasila (Peneliti.net, 2023)
Teacher professionalism is an important aspect in education that influences the quality of learning and student development. This research aims to analysis the understanding, practices, and factors influencing teacher professionalism. The research method used is qualitative research with in-depth interviews conducted with experienced teachers. The research findings indicate that the majority of teachers at SMA Negeri 3 in Central Maluku have a deep understanding of teacher professionalism and consider it as the core of their job.Factors influencing teacher professionalism include a supportive school environment, support from colleagues and school leaders, and professional development opportunities provided by educational institutions. Challenges faced by teachers in carrying out their teaching duties include high workloads and high expectations from various stakeholders. Teachers employ various strategies to enhance their professionalism, including attending training and workshops, collaborating with colleagues, reading current literature, and seeking feedback from students and parents. This research provides a deeper understanding of teacher professionalism and its implications for teaching practices and professional development.